Free-conditioning dewatering of sewage sludge through in situ propane hydrate formation. (15th November 2018) - Wu, Boran; Horvat, Kristine; Mahajan, Devinder; Chai, Xiaoli; Yang, Dianhai; Dai, Xiaohu
Abstract: The propane hydrate formation was proposed to have potentials in realizing free-conditioning dewatering of sewage sludge with implications to simultaneous clean water extraction and highly efficient volume reduction. Primarily, the investigation on phase equilibrium of propane hydrates found that the organic components of sewage sludge promoted the propane hydrate formation in terms of decreasing equilibrium pressure by up to 19.2%, compared with that in pure water. Further, the feasibility of hydrate-based dewatering was verified through the observation of propane hydrate formation in sewage sludge and also the quality analysis of water generated from decomposition of up-floated formed hydrates. The formation of up-floated propane hydrates extracted water molecules from sewage sludge into homogeneous crystal phase, which actually excluded sludge particles from hydrate phase and realized the reduction of water in sludge phase. The efficiency of water conversion into hydrates was determined by monitoring propane pressure, which indicated that 14 batch runs decreased the water content of sludge from 98.81wt.% to 44.3wt.% under free-conditioning conditions. The chemical oxygen demand, total nitrogen and total phosphorus of hydrate-extracted water were measured to be 21 ± 1 mg/L, 10.5 ± 0.2 mg/L and 0.4 ± 0 mg/L, respectively, which reflected the excellent separation performance and also indicated that the hydrate-extracted water can be directly discharged without further treatments. Finally, the unit energy consumption of hydrate-based dewatering process based on a continuous operation mode was calculated to be 2673.96 kW h/t dry solid of sewage sludge, which was nearly half of that in thermal drying process. Therefore, the propane hydrate-based process is believed to maximize the green operation of enhanced sludge dewatering while minimizing the energy and additional material consumption. Graphical abstract: Image 1 Highlights: Formation of propane hydrates in sludge was verified to be feasible and reproducible. Free-conditioning sludge dewatering can be achieved by in situ hydrate formation. Clean water extraction and low energy consumption facilitate green sludge disposal.